CHURCH AND CHURCH BUILDING: Interview-Based Meanings Among Minority Catholics, Pinang Parish, Tangerang, Indonesia - Fransiskus Sule; Karel Wunardi (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2026)
This study investigates what the church building means for the Catholic faithful of Pinang Parish, Tangerang (Archdiocese of Jakarta). Using semi-structured interviews with seventeen parishioners and a phenomenological thematic analysis, it adopts a phenomenological–theological approach to interpret how the building is lived within everyday faith. Five themes emerged: identity, communion, stability, sacredness, and fulfillment. Participants describe the new church as making the community public and recognizable (“now we can point and say, this is our church”), gathering ministries into a stable locus for fellowship and service, and relieving the insecurity of rotating or provisional worship spaces. They also speak of an atmosphere that disposes reverence and of a sense of arrival after a long struggle for official permission to build. Wallenfang’s notion of paradox clarifies this experience: the church is held together as a concrete structure and as a sacramental sign—visible and fragile, yet experienced as mediating God’s dwelling that exceeds visibility. For a minority community, the building thus embodies perseverance and joy while reconfiguring how the faithful understand themselves as Church. The study advances ecclesiological reflection on sacred architecture by offering a bottom-up account of how lay experience and contested building processes shape ecclesial self-understanding, with relevance to wider debates on disputed worship spaces in minority contexts.